Salesforce for beginners : a step-by-step guide to optimize sales and marketing and automate business processes with the Salesforce platform /: a step-by-step guide to optimize sales and marketing and automate business processes with the Salesforce platform. (2022) - Shaalan, Sharif; Royer, Timothy
No abstract available